Unjuk kerja kulkas termoelektrik dengan rangkaian seri dan paralel pada beban air 1500 ml - Ananta, Hendra; Padang, Yesung Allo; Mirmanto, M. (Dinamika Teknik Mesin, 2017)
Along with the increase of human mobility, the portable refrigerator becomes very important because it can be used to store goods or drinks to be durable or cooler. Therefore, a refrigerator using thermoelectric is an option. Thermoelectric fridge besides easy to carry anywhere is also easy maintenance, durable, more compact, lightweight, no heavy rotating components, no use of freon and small power. Refrigerator research with thermoelectric has been done with series and parallel electric circuits to know the effect of the circuit difference to the performance of refrigerators. This study uses a mini fridge with an overall dimension of 40.8 cm x 32.6 cm x53.8 cm and with 2 thermoelectric modules TEC1-12706 model. The electrical power used for each circuit is about 12 W. The data retrieval in the test uses DAQ MX 9714 NI data logger which is connected to the PC using LabView program. The results show that the test research with a water load of 1500 ml results in the temperature of the refrigerator room of about 22.54oC for the series and 23.10oC for the parallel. While the value of COP obtained with the series circuit is 0.45 and with the parallel circuit is 0.4. There is no effect of the form of the circuit on the performance of the refrigerator.